KEANEKARAGAMAN SERANGGA HAMA PADA TANAMAN PADI DENGAN APLIKASI Streptomyces sp. DAN Trichoderma sp. DI DESA MOJOTENGAH KABUPATEN GRESIK - Alifta Wiranthi; Penta Suryaminarsih; Wiwin Windriyanti (Plumula : Berkala Ilmiah Agroteknologi, 2021)
Rice plants are often disturbed by plant-disturbing organisms (OPT) which results in decreased quality and quantity of rice production. efforts to increase the production of materials, in order to obtain production results with high quality and strength is by means of integrated pest control (IPM). The problem of pests and plant diseases is an inseparable part of plant cultivation. The use of biological agents is very cost effective and reduces the negative effects caused by the use of chemical pesticides. Microorganisms are biological agents capable of controlling insect pests. Genus Steptomyces sp. and Trichoderma sp. produce the enzyme chitinase. This study aims to determine the effect of the biological agency application Streptomyces sp. and Trichoderma sp. on the type, composition, and population of insects, the index of pest diversity on rice fields in Mojotengah Village, Gresik Regency. This study used a survey method using direct observation, insect capture was carried out using a sweep net, a yellow sticky trap, and a pitfall trap. The results of research on rice fields with insect populations found on land with biological agency applications were 280 individuals and 775 individuals without biological agency. Application of biological agents to Streptomyces sp. and Trichoderma sp. affect the number of pest populations. Application of biological agents to Streptomyces sp. and Trichoderma sp. effect on the index value of species diversity including the medium category, the evenness index on the two lands is in the medium category, the species richness index shows the high species richness level in both lands, the dominance index shows the value is included in the medium category.